A comprehensive approach to determining BER capacities and their change with aging in Drosophila melanogaster mitochondria by oligonucleotide microarray. Issue 9 (15th March 2014) - Garreau-Balandier, Isabelle; Lefebvre, Mathilde; Jacquard, Sophie; Caillat, Sylvain; Cruz-Rodriguez, Luis; Ishak, Layal; Agier, Virginie; Morel, Frédéric; Lachaume, Philippe; Dubessay, Pascal; Sauvaigo, Sylvie; Alziari, Serge; et al.
Abstract : DNA repair mechanisms are key components for the maintenance of the essential mitochondrial genome. Among them, base excision repair (BER) processes, dedicated in part to oxidative DNA damage, are individually well known in mitochondria. However, no large view of these systems in differential physiological conditions is available yet. Combining the use of pure mitochondrial fractions and a multiplexed oligonucleotide cleavage assay on a microarray, we demonstrated that a large range of glycosylase activities were present in Drosophila mitochondria. Most of them were quantitatively different from their nuclear counterpart. Moreover, these activities were modified during aging. Abstract : Modified oligonucleotide chips are able to measure BER activities in mitochondria. Mitochondrial and nuclear BER activity profiles (types and values) are different. Endonuclease is the major BER activity in Drosophila nucleus and mitochondria. In Drosophila,  aging is associated with a change in mitochondrial DNA repair capacities.